Regionalne uwarunkowania powstawania klastrów - Pasieczny, Jacek (Regional Factors Influencing Cluster Creation, 2006)
The aim of this paper is to present different ways of cluster creation. An emphasis is put on endo- and exogenous factors that are conducive to clusters' emergence. In the nineties the conditions for exogenous development of groups in SSE were created in Poland. This was supposed to support economic activities in weaker regions. Paradoxically, the exogenous creation of clusters can be observed in highly developed regions with strong industrial traditions or in big urban areas. The endogenous way of clusters creations dominates in weaker, traditionally underdeveloped regions with weak entrepreneurial climate. In the article the explanations of these phenomena are presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 547-554